Physics Learning Utilizing VIRRIC (Virtual Reality Hydroelectric): Effects on Students' Learning Outcomes and Experiences - Aminudin Zakaria; Mita Anggaryani; Tinezia Cendani; Nina Fajriah Citra (Journal of Digitalization in Physics Education, 2026)
Objective: This study explores the impact of physics learning using VR-based media on students' learning outcomes and learning experiences. This study also examined gender differences in gains. Method:  This study uses the one-group pre-test and post-test methods to measure learning outcomes and a questionnaire to determine student responses. These student responses assess how students experience learning after using the Virtual Reality Hydroelectric (VIRRIC) media. This paper reports on the design, implementation, and impact of applying VIRRIC. VIRRIC was created using MilleaLab Creator software, a VR platform inspired by the Karangkates Hydroelectric Power Plant. The inspiration for this real renewable energy product is to support students in contributing to SDG 7. VIRRIC was tested in science class learning, and 30 high school students were tested. Results:  The trial results showed that 93% of students had a moderate n-gain (average n-gain = 0.433), indicating a decent increase in learning outcomes before and after using VIRRIC. In addition, the application of VIRRIC was well received by the students, with a questionnaire score of 0.76, indicating that they had good learning experiences in physics through VIRRIC. Both results show a positive correlation between STEM activities using VIRRIC and students' learning outcomes and learning experiences. Therefore, VIRRIC can be a medium for teaching, particularly on the renewable energy topic. Novelty: This study provides scientific evidence of VR technology's effectiveness in supporting physics learning. It provides empirical evidence of how conventional physics learning can be transformed into digitalization using VR.